2020
DOI: 10.1111/joor.13036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chewing exercises on the occlusal force and masseter muscle thickness in community‐dwelling Koreans aged 65 years and older: A randomised assessor‐blind trial

Abstract: Chewing exercises have been applied in clinical settings to improve the occlusal force and function of the masseter muscle in elderly individuals. However, the clinical relevance and effects of chewing exercises are unclear. This study aimed to investigate the effects of bilateral chewing exercises on the occlusal force and masseter muscle thickness in community‐dwelling Koreans aged 65 years. Forty community‐dwelling healthy elderly individuals were enrolled in this study. They were assigned to the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Furthermore, it has been reported that chewing exercises for older people with 24 or more remaining teeth improved MOF [27]. In this study, we targeted older adults with missing teeth and found an improvement in MOF, which was consistent with previous studies [14,27].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it has been reported that chewing exercises for older people with 24 or more remaining teeth improved MOF [27]. In this study, we targeted older adults with missing teeth and found an improvement in MOF, which was consistent with previous studies [14,27].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that the loss of muscle mass is associated with the loss of strength [ 30 ] and functional impairment [ 14 ] in older adults. Another study demonstrated that masseter muscle thickness and occlusal force can simultaneously improve with chewing exercise [ 31 ]. Considering the above findings, it is biologically plausible that SMM has direct effects on e-MMM and that e-MMM has direct effects on masseter muscle strength and function, as shown in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason is that bite force is a direct reflection of the masticatory muscle strength, while mastication depends on many factors other than muscle strength. It is believed that resistance training, like chewing or clenching exercise, can provoke a myophysiological response of masseter muscle fibers, which leads to increased muscle strength and thickness (Kim et al 2020; Park et al 2020). Nevertheless, mastication is a complicated process requiring the coordinated movements of the lips, jaw, tongue, cheek, soft palate, and the masticatory muscles, which can also be affected by other factors such as the dentition status and gustatory sense.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the included studies are shown in Table 1. They were published in English (17/18) and Japanese (1/18) and were conducted in 7 countries, namely, Japan (Kawamura and Horio 1989;Ibayashi et al 2008;Sugiyama et al 2013;Ohara et al 2015;Nakagawa et al 2017;Shirai et al 2018;Matsubara et al 2021;Matsuo et al 2021), South Korea (Cho et al 2012;Kim et al 2019Kim et al , 2020Kim et al , 2021Park et al 2020), United States (Yurkstas 1953;Thompson et al 2001), Sweden (Tzakis et al 1989;Kiliaridis et al 1995;He et al 2013), Greece (Tzakis et al 1989;Kiliaridis et al 1995), China (Liu et al 2017), and Denmark (Baram et al 2020). Among the included studies, 12 studies were conducted on elders (≥65 y), and most of them were community-dwelling elders; 6 studies involved young adults (19-35 y) who were mainly university students and staff.…”
Section: Included Studiesmentioning
confidence: 99%